1986
DOI: 10.1175/1520-0477(1986)067<1362:cgifdm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Generated Imagery for 4-D Meteorological Data

Abstract: The University of Wisconsin-Madison Space Science and Engineering Center is developing animated stereo display terminals for use with McIDAS (Man-computer Interactive Data Access System). This paper describes image-generation techniques which have been developed to take maximum advantage of these terminals, integrating large quantities of four-dimensional meteorological data from balloon and satellite soundings, satellite images, doppler and volumetric radar, and conventional surface observations. The images h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Early approaches in the 1970s and 1980s used mainframe computers to create 3-D views or animations of atmospheric observations and numerical model output (e.g. Grotjahn and Chervin, 1984;Hibbard, 1986;Papathomas et al, 1988;Hibbard et al, 1989;Schiavone and Papathomas, 1990, and references therein). For example, Wilhelmson et al (1990) created an award-winning (cf.…”
Section: -D Visualization In Meteorologymentioning
confidence: 99%
“…Early approaches in the 1970s and 1980s used mainframe computers to create 3-D views or animations of atmospheric observations and numerical model output (e.g. Grotjahn and Chervin, 1984;Hibbard, 1986;Papathomas et al, 1988;Hibbard et al, 1989;Schiavone and Papathomas, 1990, and references therein). For example, Wilhelmson et al (1990) created an award-winning (cf.…”
Section: -D Visualization In Meteorologymentioning
confidence: 99%
“…Meteorological Data Visualization Meteorological data visualization has become an important topic since tens of years ago [13,29]. Many practical visualization tools have been developed to support domain research, such as Vis5D [12], Ferret [10] and GRADS [1].…”
Section: Related Workmentioning
confidence: 99%
“…Desjardins and Hasler (1980), Hasler (1981) and Hasler et al (1988) have demonstrated the use of false and real video stereo using data from geostationary satellite platforms to yield three-dimensional (3-D) renditions of cloud and storm systems. Hasler et al (1985), Hibbard (1986), andVonder Haar et al (1988) have demonstrated advanced perspective imaging techniques involving the application of shading along with false stereo to encompass the video screen viewer within four-dimensional (4-D) data assimilations of weather systems. Also, Grotjahn and Chervin (1984) have shown how wire-frame graphics and shading can be used to animate high band-width streams of numerical model data.…”
Section: Bulletin American Meteorological Societymentioning
confidence: 99%